Serum Phosphate Level in Patients with Septic Shock - Abubakar Farooq; Bilal Ahmed Bajwa; Syed Waqas Haider Naqvi; Asif Mehmood; Ahmad Sohail Dar; Azhar Ali; Zaman, Asad; Iqbal, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the association and impact of serum phosphate on outcomes and ICU-mortality in patients with sepsis and septic shock.Study Design: Prospective analytical study.Place and Duration of Study: Department of Medicine and Intensive Care, Pak-Emirates Military Hospital Rawalpindi, Pakistan, from Jan to Jun 2023.Methodology: Patients of either gender aged 18 to 70 years admitted with sepsis or septic shock in medical HDU and ICU were included. Sequential Organ Failure Assessment (SOFA) score, Acute Physiology, Age and Chronic Health Evaluation (APACHE-II) score and serum phosphate levels were noted within first 24 hours of admission. Impact of serum phosphate on disease severity and association with in-hospital mortality was analyzed with Odds ratio.Results: Three hundred patients of sepsis or septic shock were admitted with mean age 46.93±13.57 years, including 170(56.7%) males and 130(43.3%) females. Respiratory system was main focus of infection in 110(36.7%) patients, followed by gastrointestinal system in 73(24.3%). Eighty (26.7%) patients expired among which 42(41.2%) had raised serum phosphate levels, 27(31.1%) had low phosphate and 11(9.9%) had normal phosphate levels (p